REVEALED COMPARATIVE ADVANTAGE OF SELECTED AGRICULTURAL COMMODITIES OF PAKISTAN - A. Ali; W. Akhtar; S. Ahmad; C. Honghua (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2020)
Since, Pakistan is bound to follow the international agreement drafted by WTO (World Trade Organization) to formulate trade policy which should be based on comparative and competitive advantages in the international economy, therefore the present study was designed to examine the specialization and competitiveness of Pakistan’s major crops.  For this purpose, Bela’ Balassa’s (1965) indexes of Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA) were employed, and moreover, secondary data from reliable sources related to crops from 1980 to 2013 were extensively utilized. The major findings of this research study revealed that Pakistan has a strong comparative and competitive advantage in rice, onion, dates, mango, mangoes- teen and guava during the period ranging from 1980 to 2013. Similarly, Pakistan has higher competitiveness in rice and mango at international level. Results also indicated that Pakistan has been facing disadvantages in potatoes during 1980 to 1997, and banana during 1980 to 2009, however, it was maintained but these vegetables/fruits have no competitiveness in the international market. The present study concludes that Pakistan has an excellent capability (being and agriculturally based economy) of higher growth of these products; therefore, these agricultural items could prove themselves a good source for Pakistan to earn higher foreign exchange.